Ketentuan Pemberian Izin Usaha Penambangan Nikel berdasarkan Undang-Undang Tentang Perlindungan dan Pengelolaan Lingkungan Hidup dan Implementasinya di Kabupaten Konawe Kepulauan Provinsi Sulawesi Tenggara - Salsabila Khansha; Frency Siska (Bandung Conference Series: Law Studies, 2024)
ABSTRACT Every individual has the right to enjoy physical and mental well-being, have decent housing, and live in a healthy environment in accordance with the 1945 Constitution. The right to protect and preserve nature has been regulated by laws oriented toward the interests of nature. The importance of nature lies in the obligation to preserve it. Despite Indonesia, especially Southeast Sulawesi, being rich in mineral resources such as nickel, the management of natural resources must comply with environmental laws and regulations. Coastal areas and small islands, including Wawonii Island, need to be preserved. However, the granting of mining permits on Wawonii Island has previously resulted in negative impacts on the local environment and community. The nickel mining company, PT Gema Kreasi Perdana (PT GKP), resumed operations on Wawonii Island in 2018, creating controversy by violating regulations, such as the prohibition of mineral mining on small islands that could harm the environment and surrounding communities. The local government of Konawe Regency issued a Regional Regulation (Perda) supporting mining activities, despite conflicting with higher legal regulations. The impacts of PT GKP's activities, such as water pollution, have led to a clean water crisis, forcing residents to buy bottled water. Residents filed a lawsuit in the Administrative Court (PTUN) Kendari, and the Supreme Court (MA) annulled the Regional Regulation supporting mining on Wawonii Island. Nevertheless, PT GKP filed a judicial review against Law No. 27/2007, which prohibits mining activities on small islands. This research aims to analyze the provisions for granting nickel mining business permits in the coastal areas of Konawe Regency based on the Environmental Protection and Management Law. Additionally, the study aims to analyze criminal accountability for damage to water sources on the coastal areas due to nickel mining activities, based on the Environmental Protection and Management Law. The research results are expected to contribute both theoretically and practically. Theoretically, the research is expected to contribute to scientific knowledge, especially in the context of granting mining permits on small islands. Practically, the research findings are expected to serve as a foundation for local governments, mining companies, and communities to understand and address the environmental damage resulting from nickel mining activities in Konawe Regency.